Kajian Tingkat Konflik pada Pergerakan Keluar-Masuk KA Komuter di Stasiun Terminus (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Terminus station is a railway station that becomes the starting/ending point of a train journey. Bogor Station is one of the terminus stations that is very busy for Jabodetabek Commuter Train (KRL) trips. There are 8 lines to support train departing and arriving at this station. The departure line (IV to VIII) intersects with the KRL arrival line causing a conflict route. That is, the oncoming KRL is held back by the entry signal because it prioritises the departing KRL, so it is necessary to study the level of conflict. The conflict rate method is used to analyze the level of conflict by comparing variants of complex interlocking patterns at the station using the train movement definition table. The analysis results of existing conditions with loading on each route, found a conflict rate value of 81% (out of 329 trains, 266 trains are potentially affected by conflict routes). Then “path engineering” was carried out with various alternatives. Alternative 1 by changing the track list on some trains, the conflict rate value for passing trains dropped to 79% (260 trains affected). Alternative 2 with the addition of connecting lines, the conflict rate value dropped to 77% (253 trains affected). While alternative 3 with track extension, the conflict rate value drops to 74% (243 trains affected). The results show that alternative 3 is considered more efficient in supporting train operations than alternatives 1 and 2